2006
DOI: 10.1029/2006jd007279
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of atmospheric parameters during Indian Space Research Organization Geosphere Biosphere Program Land Campaign II at a typical location in the Ganga Basin: 2. Chemical properties

Abstract: [1] This paper attempts to analyze the chemical compositions of the near surface aerosols at a typical location in the Ganga basin with an emphasis on delineating the source of aerosols in foggy/hazy conditions. Collocated measurements of a number of atmospheric and aerosol parameters along with simultaneous sampling of near surface aerosols of size less than 10 mm (PM 10 ) were made as part of an intense field campaign launched under the Indian Space Research Organization Geosphere Biosphere Program (ISRO-GBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 59 publications
5
64
1
Order By: Relevance
“…Aerosol composition was measured with the chemical analysis method over IGB during different periods of time (Tare et al, 2006;Tiwari et al, 2009;. Retrieval of columnar black carbon and organic carbon has been carried out over IGB using the AERONET data Arola et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Aerosol composition was measured with the chemical analysis method over IGB during different periods of time (Tare et al, 2006;Tiwari et al, 2009;. Retrieval of columnar black carbon and organic carbon has been carried out over IGB using the AERONET data Arola et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Highest pollution levels are usually noted along the IndoGangetic Basin (IGB), which is also a region of high population density. This region is affected by dust storms during pre-monsoon season (Dey et al, 2004), and dense fog during winter Tare et al, 2006;Das et al, 2008). North-east India is a mountainous region of the Himalayas and receives the highest amount of rainfall in the country.…”
Section: Study Regionmentioning
confidence: 99%
“…IGB also shows AOD comparable (> 0.5) to that over Thar desert. IGB is prone to dust storms in pre-monsoon season (Dey et al, 2004) and extreme fog during winter Tare et al, 2006). The dust encountered in this region can be locally generated, or transported from neighbouring countries (Misra et al, 2014a).…”
Section: Cmip5mentioning
confidence: 99%
“…(Venkataraman et al 2005;Wang and Kawamura 2006;Sharma et al 2015). Several researchers have reported carbonaceous aerosols and chemical composition of total suspended particulates in the Indian region (Kulshrestha et al1998;Venkataraman and Rao 2001;Tare et al 2006;Parashar et al 2005;Tiwari et al 2009). The studies suggested that carbonaceous aerosols contribute *30 %-35 % of the total suspended particulate mass over IGP during winter (Rengarajan et al 2007;Ram and Sarin 2010) whereas contribution of water soluble ionic component (WSIC) are of the order of 15 %-20 % (Tare et al 2006;Rengarajan et al 2007;Sharma et al 2015).…”
mentioning
confidence: 99%